2020
DOI: 10.2196/21916
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Substance Use and Instagram Participation to Inform Social Network–Based Screening Models: Multimodal Cross-Sectional Study

Abstract: Background Technology-based computational strategies that leverage social network site (SNS) data to detect substance use are promising screening tools but rely on the presence of sufficient data to detect risk if it is present. A better understanding of the association between substance use and SNS participation may inform the utility of these technology-based screening tools. Objective This paper aims to examine associations between substance use and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Peer context also exists in the less decreasing trend of alcohol and substance use [ 34 ]. In the context of substance use among adolescents, there are concerns about how social distancing affects their peer reputations [ 34 ], which means that popular adolescents are attempting to uphold group norms via solitary substance use [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peer context also exists in the less decreasing trend of alcohol and substance use [ 34 ]. In the context of substance use among adolescents, there are concerns about how social distancing affects their peer reputations [ 34 ], which means that popular adolescents are attempting to uphold group norms via solitary substance use [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peer context also exists in the less decreasing trend of alcohol and substance use [ 34 ]. In the context of substance use among adolescents, there are concerns about how social distancing affects their peer reputations [ 34 ], which means that popular adolescents are attempting to uphold group norms via solitary substance use [ 22 ]. Adolescents who are less popular, who may have less confidence that their friendships can withstand social distancing, may be more willing to engage in risky behavior, such as face-to-face substance use during a pandemic, to maintain their social status.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear whether our results indicate a bias in our model’s methodological choice (eg, use of hashtags or training procedure) or a difference in social media populations that prefer different alcohol beverages. The difference in correlations might be because of several variables, including the existence of confounding factors related to the prevalence of social media use in the underlying populations that preferentially consume beer over other alcohol types, differences in perceived acceptance of beer consumption behavior, or because of other factors that may confound alcohol and social media posting [ 89 ]. Alcohol preference is an example of having interpretable hashtag representations for a given model that may help identify behavioral differences associated with an outcome of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Spearman rho, a ranked nonparametric measure that is more robust to outliers than Pearson correlation, is used to report crude (nonadjusted) correlations [ 88 ]. Potential confounding variables previously studied in alcohol and social media use include race and sex distribution, median age, education, and income [ 37 , 89 ]. A linear regression analysis evaluated the relationship between the number of tweets per population and alcohol-related outcomes after including terms to control for confounding effects.…”
Section: Methodsmentioning
confidence: 99%
“…Communication records can convey information from social networks. Bergman et al [22] found that compared with people not using addictive substances, anyone who is at risk of drinking or taking drugs (e.g., marijuana, cocaine, and heroin) are more likely to post on Instagram. Wearable devices, such as watches, wristbands, chest straps, and transdermal patches, facilitate real-time collection of various types of data, such as biological samples, location, and physiological changes, to help researchers understand the causes and consequences of substance use [19] .…”
Section: Digital Phenotypingmentioning
confidence: 99%